Find f(a), f(a + h), and the difference quotient f(a + h) − f(a)h

, where h ≠ 0.

f(x) = 3 − 2x + 4x2

f(a) =

Correct: Your answer is correct.

f(a + h) =

????HELP f(a + h) − f(a)/h =

f(x) = 3 − 2x + 4x^2f(a+h) = 3 - 2(a+h) + 4(a+h)^2 = 3 - 2a -2h +4a^2+8ah+4h^2f(a) = 3 - 2a + 4a^2[f(a+h) - f(a)]/h = [3 - 2a -2h +4a^2+8ah+4h^2 - (3 - 2a + 4a^2)]/h=[3 - 2a -2h +4a^2+8ah+4h^2 - 3 + 2a - 4a^2)]/h= [-2h + 8ah + 4h^2]/h= 4h + 8a -2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up